Pengaruh Ekstrak Apu-apu (Pistia stratiotes) terhadap Daya Simpan Fillet Ikan Patin (Pangasius sp.) yang Disimpan pada Suhu Dingin - Olima Zega; Ace Baehaki; Herpandi Herpandi (Universitas Sriwijaya, 2017)
The purpose of this research was to determine the effect of Pistia stratiotes extract on the shelf life of Pangasius fillet during storage at low temperature. The research used Factorial Randomized Design (FRD) with two factors and two replications. The first factor was the difference immersion Pangasius fillet fresh consist Pangasius fillet with immersion Pistia strtiotes extract (A0), Pangasius fillet with immersion Pistia stratiotes extract (A1) and storage time 5, 10, 15, 20 and 25 days. The parameters observed were weight loss, whiteness, peroxide value pH, Total Volatile (TVB), and Total Plate Count (TPC). The results showed that the difference immersion of Pistia stratiotes fillet significant effect (p<0.05) to the value of weight loss, it is suspected because of the polyphenolic compounds in the Pistia stratiotes extract is capable of inhibiting the enzyme activity of the meat. Whereas, the difference in storage time significantly affected weight loss, peroxide value, TVB, and TPC. Pangasius fillets with immersion Pistia strtiotes extract still fit for consumption until the 25th day